PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, KECERDASAN SPIRITUAL DAN KECERDASAN SOSIAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI DENGAN MINAT SEBAGAI PEMODERASI - Djoko Kristianto, Gusviartina Dwi I., Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
This research aims to analyze the significance of the influence of emotional intelligence, intellectual intelligence, spiritual intelligence and social intelligence pegged to the level of understanding of accounting and analyzing students interest to moderate each intelligence against the level of understanding of accountancy Faculty of Economics University of the Slamet Riyadi. This research is a survey of the student population with faculty of Economics University of Surakarta Slamet Riyadi Accounting Courses force 2012 by sampling techniques using a purposive sampling methods i.e. type selection of samples are not random and the number of samples 51 students. Engineering data collection using the questionnaire. Data analysis techniques using a classic assumption test, multiple linear regression analysis, test F, t-test, the coefficient of determination, the absolute difference in the value of the test. The research results obtained the conclusion that emotional intelligence, intellectual intelligence, spiritual intelligence, social intelligence and significant effect against the level of understanding of regression coefficient marked with the accounting positively so that the ever increasing the intelligence of the students then can increase understanding of accounting. Variable interest students do not moderate the influence of variables against accounting understanding emotional intelligence. Student interest in moderating variables influence the intellectual quotient of variables against the understanding of accounting. Variable interest students do not moderate the influence of variable spiritual intelligence against the understanding of accounting. Variable interest students do not moderate the influence of social intelligence pegged to variable understanding of accounting.Keywords: emotional intelligence, intellectual intelligence, spiritual intelligence, social intelligence, interests and understanding of accounting student